A Systematic Review of Marine Risk Assessment: The Fuzzy Analytic Hierarchy Process (FAHP) - Parmen, A.; Abdullah, N. M (International Journal of Integrated Engineering, 2022)
This systematic review examines the marine risk assessment (MRA) by identifying the most viable method in assessing marine risks using the latest technology. This paper centers on the Fuzzy Analytic Hierarchy Process (FAHP) where the techniques and advantages of FAHP in facilitating important decisions were analyzed. A systematic review of the literature was conducted to highlight the significance and potentials of FAHP in providing a comprehensive risk assessment analysis which serves as a standard applicable guideline in the marine industry. Firstly, a systematic search in three electronic databases (Mendeley, Scopus and ScienceDirect) was performed to collect relevant literature. They are database. Upon finalizing the data, a systematic review was conducted accordingly. Drawing from various disciplines of risk assessment, this paper presents the analysis and findings of several studies employing different analytical methods using FAHP. The results of this review offer further insights and alternatives concerning hierarchical decision-making especially in the field of risk assessment.